Stress tolerance training academic aerobics model - Zuikova, E. G.; Bushma, T. V.; Ustinova, O. N. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to develop and test benefits of a new unaided stress tolerance training aerobics model for university students. Methods and structure of the study. The study involved -year 1Saint Petersburg Polytechnic University student trainees of the academic aerobics course (n=372) and surveyed them by the Y.V. Shcherbatykh questionnaire survey method to rank the key stressors, offer the stress coping methods and rate the individual stress tolerance: see Figure 1 hereunder. Note that the individual exposures to stressors were deemed determined by the stress tolerance rates.